The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1159/000351597
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Changes in Plasma Leptin Concentrations and Plasminogen Activator Inhibitor-1 in Obese Prepubertal Children after Nine Months of Treatment

Abstract: Background/Aims: The metabolic syndrome (MS) is associated with insulin resistance (IR), inappropriate fibrinolysis and high plasma leptin concentrations. The aim of this study was to quantify fibrinolysis and MS-related variables in obese prepubertal children and to evaluate changes in these variables as a result of improved body mass index (BMI), IR and leptin levels following 9 months of treatment. Methods: The homeostasis model assessment for insulin resistance (HOMA-IR), leptin, plasminogen activator inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In total, 68 studies reported metabolic measures and details of these are listed in Table , alongside the outcome(s) of interest from each study. While various glucose measures were reported, we focused on fasting‐glucose measurements for this article (56 studies), as fasting glucose is used clinically to identify prediabetes and diabetes.…”
Section: Resultsmentioning
confidence: 99%
“…In total, 68 studies reported metabolic measures and details of these are listed in Table , alongside the outcome(s) of interest from each study. While various glucose measures were reported, we focused on fasting‐glucose measurements for this article (56 studies), as fasting glucose is used clinically to identify prediabetes and diabetes.…”
Section: Resultsmentioning
confidence: 99%
“…Because of the expansion of adipose tissue and development of insulin resistance [6], inflammatory markers and cytokines are released and affect other tissues, such as the liver and skeletal muscle [7]. In obese children, lower levels of plasma adiponectin [8], as well as higher levels of leptin [9,10], C-reactive protein (CRP), tumour necrosis factor alpha (TNF-α), soluble intercellular adhesion molecule (sICAM) [11] and plasminogen activator inhibitor-1 (PAI-1) [8,10], have been observed. We hypothesise that the use of a continuous MetS score better predicts the risks of inflammation, endothelial damage, and CVD compared with the use of the classic MetS definition.…”
Section: Introductionmentioning
confidence: 99%
“…The mean value of three tests was recorded. Normal levels were 4.73 ± 0.69 ng/mL 14 . Serum glucose was measured by enzymatic assay, and values between 60 and 100 mg/dL were considered normal according to the AAP 15 .…”
Section: Methodsmentioning
confidence: 96%